The Relationship between Adult Symptoms of Attention-Deficit/Hyperactivity Disorder and Criminogenic Cognitions - Paul E. Engelhardt; Gavin Nobes; Sophie Pischedda (Brain Sciences, 2019)
The relationship between ADHD—in particular hyperactivity—and criminal behavior is well documented. The current study investigated the role of criminogenic cognitions in the explanation of this relationship by examining which symptoms of ADHD are associated with criminogenic cognitions. Community-recruited adults (N = 192) completed self-report questionnaires for symptoms of ADHD and criminogenic cognitions. Symptoms of inattention were consistently and strongly related to criminogenic cognitions. In particular, inattention was significantly related to cutoff, cognitive indolence, and discontinuity. There was also evidence that impulsivity was positively related to criminogenic cognitions, and specifically, to the power orientation subscale. In contrast, and contrary to expectations, symptoms of hyperactivity were not related to criminogenic cognitions. These results indicate that in community-recruited adults, inattention rather than hyperactivity is related to criminogenic cognitions. We discuss the implications of these findings contrasting with those of previous studies that used forensic and clinical samples.